Transient Outward K+ Current (Ito) Underlies the Right Ventricular Initiation of Polymorphic Ventricular Tachycardia in a Transgenic Rabbit Model of Long-QT Syndrome Type 1. (June 2018) - Choi, Bum-Rak; Li, Weiyan; Terentyev, Dmitry; Kabakov, Anatoli Y.; Zhong, Mingwang; Rees, Colin M.; Terentyeva, Radmila; Kim, Tae Yun; Qu, Zhilin; Peng, Xuwen; Karma, Alain; Koren, Gideon
Abstract : Background: Sudden death in long-QT syndrome type 1 (LQT1), an inherited disease caused by loss-of-function mutations in KCNQ1, is triggered by early afterdepolarizations (EADs) that initiate polymorphic ventricular tachycardia (pVT). We investigated ionic mechanisms that underlie pVT in LQT1 using a transgenic rabbit model of LQT1. Methods: Optical mapping, cellular patch clamping, and computer modeling were used to elucidate the mechanisms of EADs in transgenic LQT1 rabbits. Results: The results showed that shorter action potential duration in the right ventricle (RV) was associated with focal activity during pVT initiation. RV cardiomyocytes demonstrated higher incidence of EADs under 50 nmol/L isoproterenol. Voltage-clamp studies revealed that the transient outward potassium current (Ito ) magnitude was 28% greater in RV associated with KChiP2 but with no differences in terms of calcium-cycling kinetics and other sarcolemmal currents. Perfusing with the Ito blocker 4-aminopyridine changed the initial focal sites of pVT from the RV to the left ventricle, corroborating the role of Ito in pVT initiation. Computer modeling showed that EADs occur preferentially in the RV because of the larger conductance of the slow-inactivating component of Ito, which repolarizes the membrane potential sufficiently rapidly to allow reactivation of ICa, L before IKr has had sufficient time to activate. Conclusions: Ito heterogeneity creates both triggers and an arrhythmogenic substrate in LQT1. In the absence of IKs, Ito interactions with ICa, L and IKr promote EADs in the RV while prolonging action potential duration in the left ventricle. This heterogeneity of action potential enhances dispersion of refractoriness and facilitates conduction blocks that initiate pVTs. Abstract : Supplemental Digital Content is available in the text.